Conductive paste for terminal electrodes of multilayer ceramic electronic components
The optimized conductive paste for multilayer ceramic components addresses the challenge of uniform thickness in terminal electrode films by using copper powder and organic vehicle components, ensuring consistent film thickness and conductivity.
Patent Information
- Application Number
- JP2018225891
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2018-11-30
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2038-11-30
AI Technical Summary
Existing methods struggle to form terminal electrode films in multilayer ceramic electronic components with uniform thickness, particularly in the center and corner parts, leading to conductivity issues.
A conductive paste formulation with specific ranges for conductive powder and resin component content, viscosity, and phase difference, optimized for uniform film thickness, using copper powder and organic vehicle components.
The conductive paste ensures a terminal electrode film with suppressed thickness variation, maintaining sufficient film thickness in both center and corner parts, enhancing conductivity and stability.
Smart Images

Figure 0007620176000003 
Figure 0007620176000004 
Figure 0007620176000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive paste for forming terminal electrodes of laminated ceramic electronic components such as laminated ceramic capacitors, laminated inductors, and laminated piezoelectric elements. [Background technology]
[0002] Multilayer ceramic electronic components such as multilayer ceramic capacitors, multilayer inductors, and multilayer piezoelectric elements are generally manufactured as follows.
[0003] First, a conductive paste for internal electrodes is printed in a predetermined pattern on a dielectric ceramic green sheet such as a barium titanate ceramic. Then, a plurality of these sheets are stacked and pressed together to obtain an unfired laminate in which ceramic green sheets and internal electrode paste layers are alternately stacked. The obtained laminate is cut into chips of a predetermined shape to obtain a laminate element. Note that the laminate element may be fired at a high temperature at this stage, or may not be fired at this stage and may be fired simultaneously with a terminal electrode paste layer formed later using the conductive paste for terminal electrodes. In either case, the laminate element in a state before the terminal electrode paste layer is formed is referred to as a "laminated element."
[0004] Then, if the conductive paste for the terminal electrode is of the fired type, the conductive paste for the terminal electrode, whose components are conductive powder, binder resin, organic solvent, and glass frit added as necessary, is immersed in the conductive paste for the terminal electrode to form a terminal electrode paste layer on the exposed end surface of the internal electrode of the laminated body, and then dried and fired at high temperature to form the terminal electrode. If the conductive paste for the terminal electrode is of the non-fired type, the conductive paste for the terminal electrode, whose main components are conductive powder, binder resin using thermosetting resin or photosensitive resin that is hardened by active energy such as heat or light, and organic solvent, is immersed in the conductive paste for the terminal electrode to form a terminal electrode paste layer in the same manner as above, and then the paste is hardened by applying active energy (heating, etc.) to form the terminal electrode.
[0005] Furthermore, thereafter, a plating layer of nickel, tin or the like may be formed on the terminal electrodes by electroplating or the like as required.
[0006] Traditionally, precious metals such as palladium, silver-palladium, and platinum have been used as internal electrode materials, but there is a demand for resource conservation and cost reduction, and in sintered types in particular, there is a demand for preventing delamination and cracks caused by the oxidative expansion of palladium and silver-palladium during sintering, so in recent years, the use of base metals such as nickel, cobalt, and copper has become mainstream. For this reason, copper, nickel, cobalt, or alloys of these metals, which are likely to form good electrical connections with base metal internal electrodes, are being used as terminal electrode materials instead of the conventional silver and silver-palladium.
[0007] However, when the terminal electrode paste layer is formed by the dipping method, there is a problem that the paste layer tends to become thick near the center of the end face of the laminated element. Therefore, a blotting process is widely and commonly used in which the end face of the terminal electrode paste layer formed on the end face of the laminated element is pressed against a flat plate to shape the terminal electrode paste layer and adjust the dimensions and shape of the terminal electrode (Patent Document 1).
[0008] Since a single blot treatment may not be sufficient to achieve sufficient shaping, there are known examples of performing the blot treatment multiple times (Patent Document 2) and of preparing a conductive paste layer for the blot treatment separately from the conductive paste layer for immersion (Patent Document 3).
[0009] However, in the past, it was sometimes difficult to obtain a terminal electrode film with a uniform thickness while ensuring a sufficient film thickness at the center and corners of the terminal electrode. In such cases, breaks or the like occurred in the terminal electrode film, making it difficult to obtain stable and good conductivity. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2010-206135 A [Patent Document 2] JP 2012-28465 A [Patent Document 3] JP 2001-345240 A Summary of the Invention [Problem to be solved by the invention]
[0011] An object of the present invention is to provide a conductive paste for terminal electrodes of multilayer ceramic electronic components that can be suitably used for forming a terminal electrode film in which thickness variation is suppressed while ensuring a sufficient film thickness in the central and corner portions of the terminal electrode. [Means for solving the problem]
[0012] Such an object can be achieved by the present invention described in (1) to (9) below. (1) A conductive paste used to form terminal electrodes of a multilayer ceramic electronic component, comprising: The conductive paste includes at least a conductive powder and an organic vehicle including a resin component and a solvent, the content of the conductive powder is in the range of 55.0 parts by mass or more and 85.0 parts by mass or less, and the content of the resin component is in the range of 2.0 parts by mass or more and 10.0 parts by mass or less, when the total amount of the conductive powder and the organic vehicle is 100 parts by mass; When the conductive paste is subjected to dynamic viscoelasticity measurement at a frequency of 1.0 Hz and a strain of 0.004, the phase difference δ is 30° or more. 55 2. A conductive paste for terminal electrodes of a multilayer ceramic electronic component, comprising:
[0013] (2) Shear rate: 0.02 s -1 The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to the above (1), having a viscosity of 500 Pa·s or more and 6000 Pa·s or less at 0.5° C.
[0014] (3) Shear rate: 0.02 s -1The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to (2) above, having a viscosity of 1500 Pa·s or more and 4500 Pa·s or less at 0.5° C.
[0015] (4) The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to any one of (1) to (3) above, wherein the conductive powder is a metal powder containing copper.
[0016] (5) The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to any one of (1) to (4) above, wherein the conductive powder is a flake-shaped powder.
[0017] (6) The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to any one of (1) to (5) above, wherein the conductive powder has an average particle size of 0.1 μm or more and 10 μm or less. (7) The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to any one of (1) to (6) above, wherein the content of the resin component is within the range of 4.0 parts by mass or more and 7.0 parts by mass or less when the total amount of the conductive powder and the organic vehicle is 100 parts by mass. ( 8 ) the content of the resin component is within a range of 4.0 parts by mass or more and 6.3 parts by mass or less when the total amount of the conductive powder and the organic vehicle is 100 parts by mass, 7 2. The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to claim 1 . (9) The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to any one of (1) to (8) above, wherein the content of the conductive powder is within the range of 55.0 parts by mass or more and 81.0 parts by mass or less when the total amount of the conductive powder and the organic vehicle is 100 parts by mass. Effect of the Invention
[0018] According to the present invention, it is possible to provide a conductive paste for terminal electrodes of multilayer ceramic electronic components that can be suitably used for forming a terminal electrode film in which thickness variation is suppressed while ensuring a sufficient film thickness in the central and corner portions of the terminal electrode. [Brief description of the drawings]
[0019] [Figure 1] 2 is a scanning electron microscope (SEM) photograph of a cross section near a terminal electrode formed using the conductive paste of Example 1. [Diagram 2] 1 is a scanning electron microscope (SEM) photograph of a cross section near a terminal electrode formed using the conductive paste of Comparative Example 1. [Diagram 3] 1 is a scanning electron microscope (SEM) photograph of a cross section near a terminal electrode formed using the conductive paste of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be described in detail below based on preferred embodiments, but the scope of the present invention is not limited to these embodiments.
[0021] [Conductive paste for terminal electrodes of multilayer ceramic electronic components] The conductive paste for terminal electrodes of multilayer ceramic electronic components of the present invention is a conductive paste used for forming terminal electrodes of multilayer ceramic electronic components such as multilayer ceramic capacitors, multilayer inductors, and multilayer piezoelectric elements.
[0022] The conductive paste for terminal electrodes of a multilayer ceramic electronic component of the present invention contains at least a conductive powder and an organic vehicle comprising a resin component and a solvent.
[0023] When the total amount of the conductive powder and the organic vehicle consisting of a resin component and a solvent is 100 parts by mass, the content of the conductive powder is within the range of 55.0 parts by mass or more and 85.0 parts by mass or less, the content of the resin component is within the range of 2.0 parts by mass or more and 10.0 parts by mass or less, and the phase difference δ when dynamic viscoelasticity is measured at a frequency of 1.0 Hz and a strain of 0.004 is within the range of 30° or more and 57° or less.
[0024] With this configuration, it is possible to provide a conductive paste for terminal electrodes of multilayer ceramic electronic components that can be suitably used for forming a terminal electrode film in which thickness variations are suppressed while ensuring a sufficient film thickness in the central and corner portions of the terminal electrode.
[0025] The temperature during the dynamic viscoelasticity measurement can be 25° C. The dynamic viscoelasticity can be measured using a rheometer (for example, AR2000, manufactured by TA Instruments). The cone plate that can be used has a cone diameter of 40 mm and a cone angle of 2°.
[0026] On the other hand, if the above conditions are not met, satisfactory results will not be obtained. For example, if the content of the conductive powder is less than the lower limit, a sufficient film thickness cannot be ensured after firing, and high conductivity cannot be obtained.
[0027] Furthermore, if the content of the conductive powder exceeds the upper limit or the content of the resin component is less than the lower limit, the dispersibility of the inorganic components, including the conductive powder, in the paste decreases, and the printability of the paste decreases.
[0028] Furthermore, if the content of the resin component exceeds the upper limit, particularly in the case of a baked type paste, carbon residues are likely to be generated during baking, resulting in a decrease in electrical conductivity.
[0029] If the phase difference δ is less than the lower limit, the leveling property of the conductive paste deteriorates, making it difficult to sufficiently suppress the variation in thickness of the terminal electrodes.
[0030] Moreover, if the phase difference δ exceeds the upper limit, it becomes difficult to ensure a sufficient film thickness at the corners of the terminal electrodes.
[0031] In the following description, the "conductive paste for terminal electrodes of multilayer ceramic electronic components" will also be referred to simply as "conductive paste."
[0032] <Metal powder> The conductive paste according to the present invention contains a conductive powder.
[0033] Examples of the materials constituting the conductive powder include silver, gold, platinum, copper, palladium, nickel, tungsten, zinc, tin, iron, cobalt, and alloys containing at least one of these. The conductive powder may be a combination of two or more of the above materials.
[0034] Among these, from the viewpoints of electrical conductivity, ease of handling, and the like, the conductive powder is preferably a powder containing at least one of silver and copper, for example, silver powder or copper powder, and more preferably a metal powder containing copper.
[0035] This provides a terminal electrode formed using the conductive paste with superior electrical conductivity. In addition, when the conductive powder is a metal powder containing copper, this is advantageous in terms of production costs.
[0036] In addition to metal powder, the conductive powder may be a composite powder in which an inorganic powder such as an oxide, glass, or ceramic is coated with a metal, or a composite powder in which a metal powder is coated with an oxide, glass, ceramic, or another metal.
[0037] If necessary, the conductive powder may be a metal powder that has been surface-treated with an organometallic compound, a surfactant, a fatty acid, or the like.
[0038] Depending on the application, the conductive powder may be made of a conductive material other than metal, such as conductive carbon or conductive resin.
[0039] The conductive powder may have various shapes, such as spherical, flake, and granular, and one or more selected from these may be used in combination, with the flake shape being preferred.
[0040] The flake shape increases the specific surface area of the conductive powder, making it easier to prevent dripping during paste printing. In addition, particularly in the case of non-sintered hardening type pastes, the contact area between the conductive powder particles increases, contributing to high conductivity.
[0041] In this specification, the term "spherical" refers to a particle shape in which the ratio of major axis to minor axis is 2 or less, and the term "flaky" refers to a particle shape in which the ratio of major axis to minor axis is more than 2.
[0042] Average particle size of conductive powder (D 50 ) is preferably in the range of 0.1 μm or more and 10 μm or less, more preferably in the range of 0.3 μm or more and 5 μm or less, and even more preferably in the range of 0.5 μm or more and 3 μm or less. This can further improve the sinterability and printability of the conductive paste.
[0043] In this specification, the average particle size (D 50 ) refers to the 50% weight-based cumulative fraction of particle size distribution measured using a laser particle size distribution analyzer, unless otherwise specified, and can be determined, for example, by measurement using a laser diffraction / scattering particle size distribution analyzer LA-960 (manufactured by HORIBA Corporation).
[0044] In order to adjust the conductivity and sinterability of the conductive paste, a small amount of conductive ultrafine particles (e.g., particles with a particle size of 0.04 μm or less) may be added. However, the content of the ultrafine particles is preferably 3.0 parts by mass or less, and more preferably 1.0 part by mass or less, when the total content of the conductive powder is 100 parts by mass.
[0045] When the total amount of the conductive powder and organic vehicle in the conductive paste is 100 parts by mass, the content of the metal powder may be in the range of 55.0 parts by mass or more and 85.0 parts by mass or less, preferably in the range of 67.0 parts by mass or more and 82.0 parts by mass or less, and more preferably in the range of 70.0 parts by mass or more and 81.0 parts by mass or less. This allows the above-mentioned effects of the present invention to be more pronounced.
[0046] <Organic vehicle> The conductive paste according to the present invention contains an organic vehicle consisting of a resin component and a solvent.
[0047] (Resin component) Examples of the resin components constituting the organic vehicle include cellulose-based resins such as ethyl cellulose, hydroxyethyl cellulose, ethyl hydroxyethyl cellulose, and nitrocellulose, (meth)acrylic resins such as polymethyl acrylate and polymethyl methacrylate, butyral resins, phenolic resins, epoxy resins, alkyd resins, rosin esters, styrene-based resins, melamine resins, polyurethane resins, polyimide resins, polyester resins, and photosensitive monomers such as polyfunctional acrylate and polyfunctional methacrylate monomers, and one or more selected from these can be used in combination. Among these, cellulose-based resins, acrylic resins, phenolic resins, and alkyd resins are preferred.
[0048] When these resins are used, the dispersibility of the entire paste is further improved, and the variation in the applied film thickness is more effectively suppressed, resulting in more favorable film thickness at the corners.
[0049] In the conductive paste, the resin component may be contained in either a dissolved state or a dispersed state.
[0050] In addition, when the total amount of the conductive powder and organic vehicle in the conductive paste is 100 parts by mass, the content of the resin component may be 2.0 parts by mass or more and 10.0 parts by mass or less, preferably 3.0 parts by mass or more and 7.0 parts by mass or less, and more preferably 4.0 parts by mass or more and 6.3 parts by mass or less. This allows the above-mentioned effects of the present invention to be more pronounced.
[0051] (solvent) Examples of solvents constituting the organic vehicle include water, hydrocarbons, alcohols, ethers, esters, ketones, and glycols. More specifically, examples of the solvents include toluene, benzene, octanol, decanol, terpineol, terpineol acetate, dihydroterpineol, dihydroterpineol acetate, carbitol, butyl carbitol, cellosolve, butyl cellosolve, butyl carbitol acetate, cellosolve acetate, ethylene glycol diacetate, and propylene glycol diacetate. One or more of these solvents may be used in combination.
[0052] In addition, when the total amount of the conductive powder and organic vehicle in the conductive paste is 100 parts by mass, the content of the solvent is not particularly limited, but is preferably 5.0 parts by mass or more and 40.0 parts by mass or less, more preferably 12.0 parts by mass or more and 22.0 parts by mass or less, and even more preferably 14.0 parts by mass or more and 20.0 parts by mass or less.
[0053] When the total amount of the conductive powder and the organic vehicle in the conductive paste is 100 parts by mass, the content of the organic vehicle is not particularly limited, but is preferably 10.0 parts by mass or more and 45.0 parts by mass or less, more preferably 14.4 parts by mass or more and 29.0 parts by mass or less, and even more preferably 17.4 parts by mass or more and 25.3 parts by mass or less.
[0054] <Other ingredients> The conductive paste of the present invention may further contain, as necessary, glass powder, a plasticizer, a dispersant, a surfactant, etc. Furthermore, for the purpose of controlling the sintering behavior, etc., various inorganic powders and organometallic compounds may also be contained.
[0055] For example, in order to promote sintering, inorganic binders such as glass powders and metal oxides, or organometallic compounds as precursors capable of generating these during firing, may be blended in. In addition, in order to retard sintering or adjust the firing shrinkage rate, inorganic powders such as metal oxide powders and ceramic powders, for example, ceramic powders containing the same type of material as the substrate, glass-ceramic powders, metal oxide powders, and other precursor compounds thereof may be blended in.
[0056] Examples of glass powders include those having compositions such as BaO-ZnO-B2O3-based, BaO-ZnO-based, BaO-SiO2-based, BaO-ZnO-SiO2-based, BaO-B2O3-SiO2-based, ZnO-B2O3-based, BaO-CaO-Al2O3-based, PbO-B2O3-SiO2-Al2O3-based, PbO-B2O3-ZnO-based, and Bi2O3-B2O3-SiO2-based compositions, and one or a combination of two or more types selected from these may be used.
[0057] The conductive paste of the present invention is prepared by mixing and kneading the materials in a conventional manner, and uniformly dispersing the conductive powder in the organic vehicle.
[0058] As described above, the conductive paste of the present invention has a phase difference δ in the range of 30° to 57° when dynamic viscoelasticity is measured at a frequency of 1.0 Hz and a strain of 0.004.
[0059] The phase difference δ in the above range can be realized, for example, by adjusting the conditions of the constituent materials. In particular, the phase difference δ in the above range can be preferably realized by the conductive powder and the organic vehicle as the constituent components of the conductive paste satisfying the above-mentioned preferable conditions.
[0060] The phase difference δ may be within the range of 30° to 57°, preferably within the range of 33° to 54°, and more preferably within the range of 36° to 49°. This allows the above-mentioned effects of the present invention to be more pronounced.
[0061] In addition, the conductive paste of the present invention has a shear rate of 0.02 s -1 The viscosity at 200° C. is preferably in the range of 500 Pa·s or more and 6000 Pa·s or less, and more preferably in the range of 1500 Pa·s or more and 4500 Pa·s or less. This allows the above-mentioned effects of the present invention to be more pronounced.
[0062] The temperature during viscosity measurement can be 25° C. The viscosity can be measured using a rheometer (for example, AR2000, manufactured by TA Instruments). The cone plate can have a cone diameter of 40 mm and a cone angle of 2°.
[0063] According to the conductive paste of the present invention as described above, it is possible to preferably form a terminal electrode film in which thickness variations are suppressed while ensuring a sufficient film thickness at the central and corner portions of the terminal electrode.
[0064] [Formation of terminal electrodes for multilayer ceramic electronic components] Next, the formation of terminal electrodes of a multilayer ceramic electronic component using the conductive paste according to the present invention will be described.
[0065] First, a laminated element is prepared in which layers made of dielectric ceramics such as barium titanate ceramics and internal electrode layers are alternately laminated.
[0066] The laminated body can be obtained by stacking and pressing a plurality of dielectric ceramic green sheets having internal electrode layers formed by printing a conductive paste for the internal electrodes in a predetermined pattern.
[0067] The laminated body is usually cut into chips of a predetermined shape after the above-mentioned compression bonding. The laminated body may be one that has been subjected to a firing process prior to the formation of the terminal electrode paste layer described below, or may not be one that has been subjected to a firing process. In other words, the internal electrode layers that constitute the laminated body may be in a paste state when the terminal electrode paste layer is formed.
[0068] Thereafter, the conductive paste according to the present invention is applied by a dipping method to the end faces of the laminated body where the internal electrodes are exposed, to form terminal electrode paste layers.
[0069] The terminal electrode paste layer formed as described above usually tends to be thicker near the center of the end face of the laminated body, so a blot process is performed to shape the terminal electrode paste layer by pressing the terminal electrode paste layer formed on the end face of the laminated body against a flat plate and adjust the dimensions and shape of the terminal electrode.
[0070] The blotting process may be performed, for example, multiple times. Also, the terminal electrode paste layer formed on the end face of the laminated body may be pressed against the flat plate, and then the terminal electrode paste layer and the flat plate may be slid relatively before being separated from the flat plate. More specifically, for example, the terminal electrode paste layer formed on the end face of the laminated body may be pressed against the flat plate, and then the laminated body provided with the terminal electrode paste layer may be moved relatively in the surface direction of the flat plate before being separated from the flat plate.
[0071] After the above-mentioned blotting process, the terminal electrode paste layer is baked or cured by activation energy to form the terminal electrode.
[0072] For example, if the conductive paste for the terminal electrodes is of a fired type, the terminal electrode paste layer formed on the laminated body is dried and then fired to form the terminal electrodes. If the laminated body is not fired prior to the formation of the terminal electrode paste layer, that is, if the internal electrode layers constituting the laminated body are pasty, the firing process fires the internal electrode layers together with the terminal electrode paste layer.
[0073] Furthermore, when the conductive paste for the terminal electrodes is of a non-fired type, the terminal electrode paste layer formed on the laminated body is hardened by applying energy corresponding to the hardening resin contained in the conductive paste for the terminal electrodes. More specifically, when the conductive paste for the terminal electrodes contains a thermosetting resin as the hardening resin, the terminal electrode paste layer can be hardened by applying thermal energy, and when the conductive paste for the terminal electrodes contains a photosensitive resin as the hardening resin, the terminal electrode paste layer can be hardened by irradiating it with light (UV, etc.).
[0074] The drying temperature for the terminal electrode paste layer is not particularly limited, but can be, for example, 100° C. or higher and 200° C. or lower.
[0075] The firing temperature (peak temperature) of the terminal electrode paste layer is not particularly limited either, but is, for example, 600° C. or higher and 900° C. or lower.
[0076] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to these. EXAMPLES
[0077] The present invention will be described in detail below based on examples and comparative examples, but the present invention is not limited thereto.
[0078] [1] Manufacturing of conductive paste (Examples 1 to 9 and Comparative Examples 1 to 5) The conductive powder, resin component, solvent and additives were mixed in the components and compounding ratios shown in Table 1, and kneaded in a three-roll mill to produce a conductive paste.
[0079] The symbols in Table 1 are as follows: [Conductive powder A] Cu-018 (spherical copper powder with an average particle size of 2.3 μm) manufactured by Shoei Chemical Industry Co., Ltd. [Conductive powder B] Cu-521F (flake-shaped copper powder with an average particle size of 2.8 μm) manufactured by Shoei Chemical Industry Co., Ltd. [Conductive powder C] Cu-513F (flake-shaped copper powder with an average particle size of 6.7 μm) manufactured by Shoei Chemical Industry Co., Ltd. [Conductive powder D] Ag-026 (spherical silver powder with an average particle size of 1.6 μm) manufactured by Shoei Chemical Industry Co., Ltd. [Conductive Powder E] Ag-540 (flake-shaped silver powder with an average particle size of 10 μm) manufactured by Shoei Chemical Industry Co., Ltd. [Resin component A] Mitsubishi Rayon Dianale MB-2677 (acrylic resin) [Resin component B] Mitsubishi Rayon Dianall BR-105 (acrylic resin) [Resin component C] MR260IBM (acrylic resin) manufactured by Soken Chemical [Resin component D] Hercules N4 (ethyl cellulose) [Resin component E] Hercules N50 (ethyl cellulose) [Resin component F] DIC Super Beccasite 1001 (phenolic resin) [Resin component G] Showa Varnish K-2030 (alkyd resin) [Resin component H] KOREA CNC RS-20 nitrocellulose [Solvent A] Terpineol [Solvent B] Dipropylene glycol mono-n-propyl ether (DPNP) [Solvent C] Butyl carbitol [Additive] Kusumoto Chemical's HIPLAAD-ET7020 (thixotropic agent)
[0080] [Table 1]
[0081] [2] Dynamic viscoelasticity measurement The viscosity and phase difference δ of the conductive pastes of the above-mentioned Examples and Comparative Examples were determined by measurement using a rheometer (AR2000: manufactured by TA Instruments). The cone plate used had a cone diameter of 40 mm and a cone angle of 2°. The temperature condition was set at 25°C. The viscosity was measured at a shear rate of 0.02 s -1 , 2s -1 , 20s -1The phase difference δ was measured at a frequency of 1.0 Hz and strain amounts of 0.004, 0.04, and 0.4.
[0082] [3] Manufacturing of multilayer ceramic electronic components Using the conductive pastes of the respective Examples and Comparative Examples, multilayer ceramic capacitors having terminal electrode layers were manufactured as multilayer ceramic electronic components in the following manner.
[0083] First, a laminate of a barium titanate-based ceramic dielectric green sheet and nickel internal electrodes was sintered at high temperature to prepare a laminate body having planar dimensions of 3.2 mm×2.5 mm and a thickness of 2.5 mm.
[0084] On the other hand, the conductive paste was used to form a conductive paste layer having a thickness of 500 μm on a flat plate.
[0085] Next, the laminated element was lowered toward the conductive paste layer at a speed of 500 μm / s, and the end surface of the laminated element where the nickel internal electrode was exposed was immersed, and then pulled up at a speed of 100 μm / s, thereby forming a terminal electrode paste layer on the end surface of the laminated element.
[0086] Next, the laminated body was moved close to a flat plate, and the terminal electrode paste layer was lowered toward the flat plate at 500 μm / s while leaving a clearance of 250 μm between the end face of the laminated body and the flat plate. Then, with the terminal electrode paste layer still in contact with the flat plate, the laminated body was moved 8 mm in a direction parallel to the plane of the flat plate at 500 μm / s, and then the laminated body was lifted up from the flat plate at 500 μm / s.
[0087] Next, the laminate was dried in a hot air dryer at 150°C for 10 minutes, and then fired in a belt muffle furnace under conditions of a peak temperature holding time of 10 minutes and a firing time of 1 hour from start to finish to form terminal electrodes and obtain a multilayer ceramic capacitor.
[0088] In Examples 1 to 7 and Comparative Examples, in which copper powder was used as the conductive powder, the entire firing atmosphere (binder removal zone and firing zone) was a nitrogen atmosphere containing 5 ppm of oxygen, and the peak temperature was set to 780°C. In Examples 8 and 9, in which silver powder was used as the conductive powder, the entire firing atmosphere (binder removal zone and firing zone) was an air atmosphere, and the peak temperature was set to 800°C.
[0089] [4] Evaluation For the multilayer ceramic capacitors obtained in the respective Examples and Comparative Examples, a cross section near the terminal electrodes was observed by a scanning electron microscope (SEM).
[0090] FIG. 1 shows a scanning electron microscope (SEM) photograph of a cross section near a terminal electrode formed using the conductive paste of Example 1, FIG. 2 shows a scanning electron microscope (SEM) photograph of a cross section near a terminal electrode formed using the conductive paste of Comparative Example 1, and FIG. 3 shows a scanning electron microscope (SEM) photograph of a cross section near a terminal electrode formed using the conductive paste of Comparative Example 2. In these figures, a is an overall view of the vicinity of the terminal electrode, b is an enlarged view of the left corner of a, c is an enlarged view of the center of a, and d is an enlarged view of the right corner of a.
[0091] For the multilayer ceramic capacitors obtained in each of the Examples and Comparative Examples, scanning electron microscope (SEM) photographs were used to determine the film thickness (central film thickness, Tt) at the central portion of the terminal electrode (see Figures 1 to 3c), and the average film thickness (Tc [μm]) at the left corner portion (see Figures 1 to 3b) and right corner portion (see Figures 1 to 3d) of the terminal electrode, and from these results, the ratio Tc / Tt (C / T ratio) of the corner film thickness (Tc [μm]) to the central film thickness (Tt [μm]) was determined.
[0092] The overall evaluation was as follows: "The central film thickness (Tt) is 10 μm or more, Tc / Tt is 0.8 or more, and the film thickness is uniform and free of irregularities" was marked as "○", "The central film thickness (Tt) is 10 μm or more, Tc / Tt is 0.5 or more and less than 0.8, and the film thickness is uniform and free of irregularities" or "The central film thickness (Tt) is 8 μm or more and less than 10 μm, Tc / Tt is 0.8 or more, and the film thickness is uniform and free of irregularities" was marked as "△", and all other evaluations were marked as "×". These results are summarized in Table 2 together with the viscosity and phase difference data.
[0093] [Table 2]
[0094] As is clear from Table 2, in the present invention, a terminal electrode film having a sufficient film thickness at the center and corners of the terminal electrode and having reduced thickness variation could be suitably formed.
[0095] In addition, according to Table 2, 2s -1 and 20s -1 No correlation was observed between the viscosity of the resin and the effect of the present invention, and no correlation was observed between the phase difference δ at strains of 0.04 and 0.4 and the effect of the present invention.
Claims
1. A conductive paste used for forming terminal electrodes of a multilayer ceramic electronic component, comprising: The conductive paste includes at least a conductive powder and an organic vehicle including a resin component and a solvent, the content of the conductive powder is in the range of 55.0 parts by mass or more and 85.0 parts by mass or less, and the content of the resin component is in the range of 2.0 parts by mass or more and 10.0 parts by mass or less, when the total amount of the conductive powder and the organic vehicle is 100 parts by mass; A conductive paste for terminal electrodes of a multilayer ceramic electronic component, characterized in that when dynamic viscoelasticity measurement is performed on the conductive paste at a frequency of 1.0 Hz and a strain of 0.004, the phase difference δ is in the range of 30° or more and 55° or less.
2. Shear rate 0.02 s -1 2. The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to claim 1, wherein the viscosity at 2000 Pa·s is from 500 Pa·s to 6000 Pa·s.
3. Shear rate 0.02 s -1 3. The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to claim 2, wherein the viscosity at 2000° C. is from 1,500 Pa·s to 4,500 Pa·s.
4. 4. The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to claim 1, wherein the conductive powder is a metal powder containing copper.
5. 5. The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to claim 1, wherein the conductive powder is in the form of flakes.
6. 6. The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to claim 1, wherein the conductive powder has an average particle size of 0.1 μm or more and 10 μm or less.
7. 7. The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to claim 1, wherein the content of the resin component is in the range of 4.0 parts by mass or more and 7.0 parts by mass or less when the total amount of the conductive powder and the organic vehicle is 100 parts by mass.
8. 8. The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to claim 1, wherein the content of the resin component is in the range of 4.0 parts by mass or more and 6.3 parts by mass or less when the total amount of the conductive powder and the organic vehicle is 100 parts by mass.
9. 9. The conductive paste for terminal electrodes of a multilayer ceramic electronic component according to claim 1, wherein the content of the conductive powder is in the range of 55.0 parts by mass or more and 81.0 parts by mass or less when the total amount of the conductive powder and the organic vehicle is 100 parts by mass.
Citation Information
Patent Citations
Conductive paste and ceramic electronic component
JP2001023438A
Method and device for forming end electrode of chip-like electronic parts
JP2001345240A
Conductive paste and laminated ceramic electronic part
JP2003124052A
Conductive paste and multilayer ceramic electronic component
JP2003303734A
Conductive resin composition and conductive paste
JP2005264095A